WAWANCARA KOGNITIF UNTUK ADAPTASI INSTRUMEN COPENHAGEN BURNOUT INVENTORY PADA TENAGA KESEHATAN INDONESIA - Har Yudha (Jurnal Medika Hutama, 2021)
In health care fields, burnout have negative impacts not only on self health, but also on patient’s healthcare. CBI is one of instruments in assessing burnout which has been widely referenced in previous study and highly adopted on several languages. This study aims to adopt CBI instrument so that can be used to measure burnout on health care workers in Indonesia. The adaptation process begins with forward translation and back translation from professional translator. After that, the translated instrument was pretested with cognitive interview method on 10 participant from different health care providers background. Cognitive interview conducted online with combination of verbal probing and thinking aloud to explore participant’s comprehension on every CBI items, included wording, structure of sentence, and the answer choice. There are nine items revised and adjusted to make it clear and more understandable. There is no item need to be deleted, so this CBI instrument can be used to measure burnout on Indonesian health care workers.